2016
DOI: 10.1136/annrheumdis-2016-209850
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the RhoA-ROCK pathway to reverse T-cell dysfunction in SLE

Abstract: Objectives Deregulated production of IL-17 and IL-21 contributes to the pathogenesis of autoimmune disorders like SLE and RA. Production of IL-17 and IL-21 can be regulated by ROCK2, one of the two Rho kinases. Increased ROCK activation was previously observed in an SLE cohort. Here, we evaluated ROCK activity in a new SLE cohort, an RA cohort, and assessed the ability of distinct inhibitors of the ROCK pathway to suppress production of IL-17 and IL-21 by SLE T cells or human Th17 cells. Methods ROCK activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…In addition, RhoA functions through activation of its immediate downstream effectors such as Rho‐associated protein kinase (ROCK), mDia, and protein kinase N . Blockade of ROCK activity by its specific inhibitors Y27632 or fasudil is associated with the downregulation of Th17 function and improvement for several autoimmune and inflammatory diseases, such as systemic lupus erythematosus, OVA‐induced murine allergic lung inflammation, and viral myocarditis . Thus, ROCK likely contributes to RhoA‐regulated Th17 signaling and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, RhoA functions through activation of its immediate downstream effectors such as Rho‐associated protein kinase (ROCK), mDia, and protein kinase N . Blockade of ROCK activity by its specific inhibitors Y27632 or fasudil is associated with the downregulation of Th17 function and improvement for several autoimmune and inflammatory diseases, such as systemic lupus erythematosus, OVA‐induced murine allergic lung inflammation, and viral myocarditis . Thus, ROCK likely contributes to RhoA‐regulated Th17 signaling and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…42 As we have shown that RhoA promotes mTOR signaling in activated T cells and RhoA promotes Th2 differentiation through glycolysis, 11 it will be interesting to determine whether mTOR-regulated glycolysis contributes to RhoA-mediated Th17 differentiation in future. In addition, RhoA functions through activation of its immediate downstream effectors such as Rho-associated protein kinase (ROCK), mDia, and protein kinase N. 43 Blockade of ROCK activity by its specific inhibitors Y27632 or fasudil is associated with the downregulation of Th17 function and improvement for several autoimmune and inflammatory diseases, such as systemic lupus erythematosus, 44 OVA-induced murine allergic lung inflammation, 45 and viral myocarditis. 46 Thus, ROCK likely contributes to RhoA-regulated Th17 signaling and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, while KD025 suppresses Th17 differentiation through decreased STAT3 phosphorylation, it accelerates regulatory T cell (Treg) differentiation through enhanced STAT5 phosphorylation. The effect of KD025 to suppress IL‐17 and IL‐21 production was then confirmed in PBMCs from patients with rheumatoid arthritis, graft‐versus‐host disease, systemic lupus erythematosus and inflammatory bowel diseases . Further, recent Phase 2 studies showed that oral administration of KD025 reduces clinical scores in psoriasis patients with concomitant decrease in plasma levels of IL‐17 and IL‐23 and increase in that of IL‐10 .…”
Section: Rho Signaling Research In Current Statusmentioning
confidence: 87%
“…Reduced JNK phosphorylation levels were also found in the same cells (Table 4). 39 ERM phosphorylation in humans has not been assessed previously, and its pathogenic role in HF remains unknown. [11][12][13] Our findings here also show for the first time that in patients with HFrEF, ROCK activation in PBMCs takes place predominantly in T lymphocytes, specifically in CD4 and in CD8 T lymphocytes, which is possibly related to the higher levels of ROCK-dependent pro-inflammatory molecules ICAM-1, Il-6 and IL-8.…”
Section: Rock Pathway Activation In Hfref Patientsmentioning
confidence: 99%
“…In patients with systemic inflammatory diseases, increased ROCK activity is also observed in circulating T lymphocytes. 39 ERM phosphorylation in humans has not been assessed previously, and its pathogenic role in HF remains unknown. In rodents with PBMCs was observed previously in normotensive rats with genetically increased ACE and Ang II levels, 17 which is consistent with the concept of myocardial ROCK activation mirrored in circulating leucocytes.…”
Section: Rock Pathway Activation In Hfref Patientsmentioning
confidence: 99%